Philosophy of life in the context of neonomadism: traditions and modernity - Omarova, A.T.; Mukanov, B.O.; Dauletbayeva, L.M. (NLC «Karaganda National Research University named after acad. Ye.A. Buketov», 2025)
This article examines neonomadism as a sociocultural and philosophical phenomenon that combines a nomadic lifestyle with the infrastructures of digital capitalism. It analyzes the key motivations for digital nomadism, including the desire for flexibility, freedom, and emancipation from traditional labor relations, as well as the sociopolitical aspects of this phenomenon. The study aims to philosophically reconstruct neonomadism as a form of life (Lebensform), linking it to nomadic traditions and digital technologies; identify its influence on value orientations, social mobility, and labor practices; and outline normative guidelines for policy regarding mobile labor. Using an interdisciplinary approach, this article examines the economic,social, and technological aspects of neonomadism, aiming to identify its philosophical, social, and economic aspects, as well as to understand its role in transforming notions of freedom, boundaries, and self-realization in the context of globalization and the digital economy. The study reveals that neonomadism is becoming not only a tool for professional self-realization but also an important part of the global process of labor transformation, requiring new approaches to regulation and social integration. A philosophical analysis allows us to understand the duality of the phenomenon and establish normative guidelines for mobility policy: supporting autonomy without romanticization, social guarantees without territorialization, and recognizing the nomadic contribution to cultural and economic diversity.
Social philosophy - Әлеуметтік философия - Социальная философия
Keywords: neonomadism; digital transformation; mobility; digital nomads; traditions; emancipation; socialization